Public-Private Partnerships for Elder Empowerment through Economic Productivity - Pham Hoang; Cheng Ho Lang (Borong Newinera Publisher, 2021)
Social Service and the Social Welfare Institution have a mutualistic partnership model. There are still a significant number of old individuals whose UDB IDs (unified database identifiers) have not been registered, according to Social Service and the Social Welfare Institution. Production Economic Enterprises (PEEs) is a program of the Social Service aimed at empowering communities. The Social Service and the Elderly Social Welfare Institution share responsibility for empowering communities. It is important to provide favorable conditions and an attractive environment for the elderly both inside the family and across the community as a way of demonstrating care for them. Using a productive economic business program, the social welfare institution establishes an activity group that enables the elderly to be more productive while still being able to make crafts in accordance with their abilities, thereby relieving the elderly of their burden on other communities, their families, and the government. It is being attempted to empower the elderly by developing profitable economic entrepreneurial activities in order for them to be self-sufficient. As one of the recreational activities, this lucrative economic business activity is carried out alongside other income-generating recreational activities to create a successful economic business enterprise